2016
DOI: 10.1111/gcb.13262
|View full text |Cite
|
Sign up to set email alerts
|

Towards protecting the Great Barrier Reef from land‐based pollution

Abstract: The Great Barrier Reef (GBR) is an iconic coral reef system extending over 2000 km along the north-east coast of Australia. Global recognition of its Outstanding Universal Value resulted in the listing of the 348 000 km 2 GBR WorldHeritage Area (WHA) by UNESCO in 1981. Despite various levels of national and international protection, the condition of GBR ecosystems has deteriorated over the past decades, with land-based pollution from the adjacent catchments being a major and ongoing cause for this decline. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
119
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(120 citation statements)
references
References 87 publications
1
119
0
Order By: Relevance
“…The second largest river draining into the Great Barrier Reef lagoon is the Burdekin river with a catchment area of approximately 130,000 km 2 . The Burdekin River catchment has the largest mean annual runoff and delivers the highest suspended sediment load to the Great Barrier Reef lagoon (~30% of total; Bainbridge et al, ; Kroon et al, ). The dominant land use in the Burdekin catchment is cattle grazing (>90%) across eucalypt savannah woodlands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second largest river draining into the Great Barrier Reef lagoon is the Burdekin river with a catchment area of approximately 130,000 km 2 . The Burdekin River catchment has the largest mean annual runoff and delivers the highest suspended sediment load to the Great Barrier Reef lagoon (~30% of total; Bainbridge et al, ; Kroon et al, ). The dominant land use in the Burdekin catchment is cattle grazing (>90%) across eucalypt savannah woodlands.…”
Section: Methodsmentioning
confidence: 99%
“…The dominant land use in the Burdekin catchment is cattle grazing (>90%) across eucalypt savannah woodlands. Other land modifications include irrigated cropping, horticulture and sugar cane, and mining and forestry (Bainbridge et al, ; Kroon et al, ). The Upper Burdekin and Bowen subcatchments contribute higher anthropogenic sediment yields than the other subcatchments (Bainbridge et al, ; Bartley, Croke, Bainbridge, Austin, & Kuhnert, ).…”
Section: Methodsmentioning
confidence: 99%
“…Sugarcane ( Saccharum officinarum L., 1753) is the major agricultural crop in the Wet Tropics (Kroon, Thorburn, Schaffelke, & Whitten, ), with its cultivation perceived by many as a threat to surrounding ecosystems. Several studies (Armour, Hateley, & Pitt, & G. L., ; Brodie & Mitchell, ; Haynes, Müller, & Carter, ; Haynes, Ralph, Prange, & Dennison, ; Kroon et al, ; Lewis et al, ; Mitchell, Brodie, & White, ; Tsatsaros, Brodie, Bohnet, & Valentine, ) have shown either direct impacts or threats of pesticide, nutrient and sediment runoff from sugarcane cultivation on different components of nearby coastal and marine systems. Additionally, monoculture plantations are known to be highly dissimilar from natural habitats in both composition and structure (Anand, Krishnaswamy, Kumar, & Bali, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the north, the reefs are found close to the coast (within 100 km), while the outer reefs are found further offshore (up to 200 km) in the south (Figure 17). The GBR World Heritage Area supports 2,900 coral reefs, 1,050 islands and 46,000 km 2 of seagrass beds within its 348,000 km 2 area (Kroon et al, 2016). The diversity of ecosystems found along the length, depth and across the shelf of the GBR makes it arguably the most significant marine protected area on the planet (Day & Dobbs, 2013).…”
Section: The Values Of the Great Barrier Reefmentioning
confidence: 99%
“…Researchers continue to call for renewed efforts to manage water quality to improve the resilience of GBR to multiple stressors while global climate agreements are enacted and implemented (Brodie et al, 2017;Dale et al, 2016b;Kroon et al, 2016;Waterhouse et al, 2017). The declining health of the GBR requires urgent action to maintain its resilience in the medium term, since any mitigation of climate change will take time.…”
Section: Current Condition Of the Great Barrier Reefmentioning
confidence: 99%